Memorandum of Understanding between the International Livestock Research Institute (ILRI) and Wollo University - International Livestock Research Institute; Wollo University (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Memorandum of understanding (MOU) between the International Livestock Research Institute (ILRI) and Wollo University. On September 16, 2022, MoU was signed by Jimmy Smith, Director-General of ILRI, and Mengesha Ayene Ejigu, President of Wollo University.